POLITENESS STRATEGIES IN TEXT MESSAGES WRITTEN BY ENGLISH DEPARTMENT STUDENTS TO LECTURERS - ADY, AGUNG PRAMANA MULIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Pramana Mulia Ady, Agung. 2014.  Politeness Strategies in Text Messages Written by English Department Students to Lecturers  . Study Program of English, Universitas Brawijaya. Supervisor: Nurul Chojimah; Co-Supervisor: Muhammad RozinKeywords: Face-threatening acts, Politeness strategies, Positive politeness, Negative politeness, Short message services.Face-threatening acts are acts which in some way threaten the 'face' or self-esteem of another person. People think that all communication acts  are potentially threatening. Actually, whether  the act is threatening depends  not so much on the intent of the speaker but on the interpretation and perception of the listener.  This study investigates about Face Threatening Act and politeness strategies in  text messages sent from advisees to their advisors in English Department. The study is aimed to be the reference to student as advisees English Department in order to be more polite and to pay more attention the politeness strategies when sending the text messages to their lecturers as advisors for asking about address, requesting to meet their advisors, asking about schedule, and so on.    This study used a qualitative approach. The data of this study were the text messages from advisees to advisors  which  contained FTA and politeness strategies. In collecting the data, the writer used  grouping and coding. In data analysis, the writer group  the text messages from advisors  based on the source data. Then, the  codes to the data according to the text messages  from advisors. The coding process is as follows, naming, Message 1, Message 2. This study shows that there are two FTAs performed by advisees: requesting and reminding. Those FTAs are softened by one positive politeness strategies: offer and two negative politeness strategies: hedging, and giving deference    In conclusion, after analyzing the data from text message performed by advisees, the writer founds two FTAs from eight text messages. They are requesting, reminding, suggesting, offering. And then, the  writer found one positive politeness strategies: offer in one text messages. In this case advisees offer to advisors for accept advisee’s proposal. Next the writer found two negative politeness strategies: hedging and giving deference in seven text messages. In this case, the advisees who used negative politeness especially give deference usually mention name of the advisors, and mention of honorifics of their advisors after greeting. The writer also suggests that other studies about FTAs and Politeness strategies should be done to improve the result and the finding of the previous studies and it is better done in other genre.